DIVERSITY OF ORTHOPTERAN FAUNA IN SUGARCANE AT UDAIPUR - DHAKAD, DEVENDRA; NAGAR, RAJENDRA; JHABAR MAL; P. S. RATHORE (The Bioscan, 2014)
Investigations on the orthopteran fauna in sugarcane were carried out in the Department of Entomology, Rajasthan College of Agriculture, MPUAT, Udaipur, during August to December, 2012. The orthopteran diversity comprised 32 genera belonging to 5 families during the period of survey. Members of the family Acrididae had the highest mean density values in August (29%), September (33.50%), October (55.50%), November (33.50%) and December (23.50%). Crickets of family Gryllidae were recorded to have the maximum mean density value of 12.50 per cent during the month of October, 2012. The families Pyrgomorphidae, Tetrigidae and Tettigonidae were thinly populated and thus had low mean density values. Among Acrididae, the relative density was the highest for the genus Hieroglyphus (10.02 to 16.47%) followed by that for Oxya (10.03 to 13.18%) and Spathosternum (8.07 to 12.61%). Similarly, among the gryllids, the genus Trigonidium was more abundant (29.30 to 36.70%); among pyrgomorphids, the genus Chrotogonus (42.58 to 49.99%); whereas, genera of Tetrigidae and Tettigonidae had an almost equal representation throughout the period of observation. The Shanon-Wiener Index values of diversity did not differ much for the months within the Acrididae ranging from 2.02 to 2.28; as well as among the different families of Orthoptera ranging from 2.87 to 3.01.